(untitled) (Bangladesh Journal of Animal Science, 2015)
The present study was undertaken to know the effect of pellet and mash feeding on nutrient digestibility, growth performance and carcass weight of growing rabbits. For this purpose fifteen crossbred New-Zealand white rabbit were selected for conducting the experiment. The Average ages of these experimental rabbits were 1.5 to 2.0 months. All the rabbits were housed in Quonset style cages. Animals were distributed to mash (T1), pellet (T2) and mixture of pellet and mash (T3) groups equally with five animals in each group. All the animals were supplied ad libitum green grass. The experiment shows that highest body weight was found from pelleted group. Growth rate of different dietary treatment differ significantly (p<0.05). FCR of different dietary groups did not differ significantly. Carcass weight and dressing yield of rabbits did not differ significantly, but dressing yield was highest for pelleted group. So the study reveal that, feeding of pelleted diet resulted in higher growth rate, growth velocity, dressing yield, better feed conversion efficiency compared to mash and pellet with mash. Bang. J. Anim. Sci. 2015. 44(2): 100-105